2003
DOI: 10.1007/s00534-002-0785-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of d-allose against ischemia reperfusion injury of the rat liver

Abstract: D-allose exerted its protective effects against liver damage incurred when the liver was injured by warm ischemia and reperfusion mainly by the suppression of activated neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…The biological effects of rare sugars such as D-allose have recently been investigated in detail (Hossain et al 2003;Hirooka et al 2006). We also reported that D-allose attenuates renal I/R-induced injury by suppressing neutrophil activation in normoglycemic rats (Ueki et al 2007).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The biological effects of rare sugars such as D-allose have recently been investigated in detail (Hossain et al 2003;Hirooka et al 2006). We also reported that D-allose attenuates renal I/R-induced injury by suppressing neutrophil activation in normoglycemic rats (Ueki et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Recently, some groups have focused their attention on the biological functions of rare sugars (Hossain et al 2003;Hirooka et al 2006). Rare sugars are defined as monosaccharides that exist in nature but are present only in limited quantities.…”
mentioning
confidence: 99%
“…Meanwhile, the physiological effects of rare sugars, such as shown to protect against inflammatory and oxidative ischemia/ reperfusion (I/R) injury in liver, retinal, and cerebral injuries in rodent models (Hossain et al, 2003;Hirooka et al, 2006;Gao et al, 2013). Previous studies have revealed the physiological benefits …”
Section: Introductionmentioning
confidence: 99%
“…For example, d-allose has been shown to protect against inflammatory and oxidative ischemia/ reperfusion (I/R) injury in liver, retinal, and cerebral injuries in rodent models (Hossain et al, 2003;Hirooka et al, 2006;Gao et al, 2013). Previous studies have revealed the physiological benefits of d-allose, including anti-inflammatory effects resulting from reduced myeloperoxidase (MPO) activity and reduced adherent neutrophils in organs (Hossain et al, 2003), and anti-oxidant effects resulting from reduced production of H 2 O 2 or O 2 _ (Hirooka et al, 2006;Mizote et al, 2011). Intake of anti-inflammatory or anti-oxidant compounds can be used to prevent the development of NAFLD/NASH (Park et al, 2011;Ni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation